The ethics of data collection and analysis - Mark, Melvin M.; Eyssell, Kristen M.; Campbell, Bernadette (My University, 2004)
This chapter focuses on ethical issues that can arise in the collection and analysis of data in evaluations. We move beyond common ethical issues in data collection and analysis, such as informed consent and coercion, to address four issues: the application of cost-benefit thinking to judgments about research ethics, the quality of research design as an ethical issue, the need to explore one's data, and the censoring of data.